Migrating Focal Seizures and Myoclonic Status in ARV1-Related Encephalopathy. (June 2021) - Darra, Francesca; Lo Barco, Tommaso; Opri, Roberta; Parrini, Elena; Bianchini, Claudia; Fiorini, Elena; Simonati, Alessandro; Dalla Bernardina, Bernardo; Cantalupo, Gaetano; Guerrini, Renzo
Abstract : Objective: To report longitudinal clinical, EEG, and MRI findings in 2 sisters carrying compound heterozygous ARV1 mutations and exhibiting a peculiar form of developmental and epileptic encephalopathy (DEE). Neuropathologic features are also described in one of the sisters. Methods: Clinical course description, video-EEG polygraphic recordings, brain MRI, skin and muscle biopsies, whole-exome sequencing (WES), and brain neuropathology. Results: Since their first months of life, both girls exhibited severe axial hypotonia, visual inattention, dyskinetic movements, severe developmental delay, and slow background EEG activity. Intractable nonmotor seizures started in both at the eighth month of life, exhibiting the electroclinical characteristics of epilepsy of infancy with migrating focal seizures (EIMFS). In the second year of life, continuous epileptiform EEG activity of extremely high amplitude appeared in association with myoclonic status, leading to severely impaired alertness and responsiveness. Repeated brain MRI revealed progressive atrophic changes and severe hypomyelination. WES identified a compound heterozygous in the ARV1 gene [(p.Ser122Glnfs*7) and (p.Trp163*)] in one patient and was subsequently confirmed in the other. Both sisters died prematurely during respiratory infections. Postmortem neuropathologic examination of the brain, performed in one, revealed atrophic brain changes, mainly involving the cerebellum. Conclusions: This report confirms that biallelic ARV1 mutations cause a severe form of DEE and adds epilepsy with migrating focal seizures and myoclonic status to the spectrum of epilepsy phenotypes. Considering the potential role of human ARV1 in glycosylphosphatidylinositol (GPI) anchor biosynthesis, this severe syndrome can be assigned to the group of inherited GPI deficiency disorders, with which it shares remarkably similar clinical and neuroimaging features. ARV1 should be considered in the genetic screening of individuals with EIMFS.